Strong electron–phonon coupling in magic-angle twisted bilayer graphene - Chen, Cheng; Nuckolls, Kevin P.; Ding, Shuhan; Miao, Wangqian; Wong, Dillon; Oh, Myungchul; Lee, Ryan L.; He, Shanmei; Peng, Cheng; Pei, Ding; Li, Yiwei; Hao, Chenyue; et al. (Nature (London), 2024)
The unusual properties of superconductivity in magic-angle twisted bilayer graphene (MATBG) have sparked considerable research interest 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 – 13 . However, despite the dedication of intensive experimental efforts and the proposal of several possible pairing mechanisms 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 – 24 , the origin of its superconductivity remains elusive. Here, by utilizing angle-resolved photoemission spectroscopy with micrometre spatial resolution, we reveal flat-band replicas in superconducting MATBG, where MATBG is unaligned with its hexagonal boron nitride substrate 11 . These replicas show uniform energy spacing, approximately 150 ± 15 meV apart, indicative of strong electron–boson coupling. Strikingly, these replicas are absent in non-superconducting twisted bilayer graphene (TBG) systems, either when MATBG is aligned to hexagonal boron nitride or when TBG deviates from the magic angle. Calculations suggest that the formation of these flat-band replicas in superconducting MATBG are attributed to the strong coupling between flat-band electrons and an optical phonon mode at the graphene K point, facilitated by intervalley scattering. These findings, although they do not necessarily put electron–phonon coupling as the main driving force for the superconductivity in MATBG, unravel the electronic structure inherent in superconducting MATBG, thereby providing crucial information for understanding the unusual electronic landscape from which its superconductivity is derived. Angle-resolved photoemission spectroscopy of superconducting magic-angle twisted bilayer graphene reveals flat-band replicas that are indicative of strong electron–phonon coupling; these replicas are absent in non-superconducting twisted bilayer graphene.